Sir Thomas Browne : a Study in Religious Philosophy. - Dunn, William P. (University of Minnesota Press, 1950)
This original and perceptive study of the writings of the great seventeenth-century author of Religio Medici offers the general reader a view of the intellectual world of Brownes time, and for the special student of the period provides a more extended ex.